Analysis of The Effect Evaporator Fan Rotation Variations on Air Blast Freezer Performance for Freezing Mango Puree - Wardika; Yudhy Kurniawan; Aa Setiawan; Muchammad Zuhda Alifun Naja (Logic : Jurnal Rancang Bangun dan Teknologi, 2024)
Mangoes are the main commodity in Indramayu Regency, but they are easily damaged after harvesting due to improper mango processing. One solution to overcome this problem is to process mangoes into puree. This process requires freezing technology such as an air blast freezer machine. The evaporator fan functions to prevent blocking of the evaporator fins and distribute cold air so that the room temperature reaches -18˚C. This research aims to determine the effect of variations in evaporator fan rotation on the performance of the air blast freezer system. Data are taken every 10 minutes until the mango puree reaches the set point temperature. Three experiments were conducted with evaporator fan speeds set to low (1800 RPM), medium (2200 RPM), and high (2600 RPM). Based on the tests that have been carried out, the system performance at low fan rotation produces an actual Coefficient of Performance (COP) of 1.9 with an efficiency of 41% and electricity costs of IDR 462,900. Medium fan rotation produces an actual COP of 2.0 with an efficiency of 43% and electricity costs of IDR 469,380. High fan rotation produces an actual COP of 2.1 with an efficiency of 45%. This research shows how variations in fan speed affect the COP, system efficiency, and operational costs, therefore the results of this research contribute to the development of energy efficient and economical cooling technology, especially for tropical-based food preservation applications such as fruit puree mango.